Sublay and Onlay Mesh Application Compared with Tension Free Suture as Treatment Techniques for Ventral Hernia in Sheep - Ahmed Kadhim Munahi (Journal of Global Pharma Technology, 2018)
The present study was assigned to find the optimal surgical repair for reconstruction of experimentally induced ventral hernia in sheep. A ventral hernia (5×5) cm had been made in the right flank of 9 ewes and left for a month. After that those ewes were randomly divided into 3 treatment groups; the first group of ewes was applied with polypropylene mesh repair by onlay technique. Whereas the second group was applied with polypropylene mesh repair using sublay technique. While in the third group the hernia was repaired with tension free sewing technique using catgut. The postoperative complications were monitored for a month following the previous applications. Macroscopic results showed that recurrence of hernia was experienced in the first and the third groups accompanied by wound infection and fever.  On the other hand, the second group did not face life threatening problems but experienced mild seroma and fever. There was no recorded mortality case until the end of the experiment in all treatment groups. Histologically, the onlay group demonstrated reaction of granulomatous foreign body response with process of fibrosis. In contrast, the sublay group revealed a separate granulomatous foreign body reaction and minimal response of inflammation and fibrosis. Whereas, the third group showed hyperemic blood vessels, abundance of fibrous connective tissue and deposition of collagen as well as inflammation around the suture materials. These results revealed the success of the sublay technique over the onlay and the catgut suture for herniorrhaphy.Keywords: Onlay, Sublay, Tension free suture, Ventral hernia, Sheep.